Gestione e trattamento delle fratture acetabolari - Pascarella, R.; Cerbasi, S.; Sangiovanni, P.; Fantasia, R.; Buharaja, R.; De Marco, R.; Riccardi, M.; Arduini, M. (Lo Scalpello - Journal, 2019)
MANAGEMENT AND TREATMENT OF ACETABULAR FRACTURES Acetabular fractures are complex lesions and they require anatomical surgical reduction in order to achieve satisfactory results in long-term follow-up. Some risk factors are associated with unfavourable results and have confirmed that older patients with acetabular fractures have worse outcomes than younger patients. Total hip replacement after an acetabular fracture generally produces good clinical results; however, in some contexts it must be combined with correct stable fixation of the fracture. The type of fracture and overall patient conditions influence the choice of the surgical technique and, consequently, the type of healing to lead to a satisfactory result.